Oreocharis yangjifengensis (Gesneriaceae), a new species from Yangjifeng National Nature Reserve of Yingtan City, Jiangxi Province, China - Li, Rui-Feng; Le, Xin-Gui; Xu, Lin; Maciejewski, Stephen; Chen, Bin; Wen, Fang (Phytotaxa, 2023)
Oreocharis yangjifengensis F.Wen & B.Chen, a new species of Gesneriaceae from Yangjifeng National Nature Reserve, Yingtan city, Jiangxi province, East China, is described and illustrated. It can be easily distinguished from other Oreocharis species by having a zygomorphic and urceolate corolla, and peduncle, bracts, pedicel and calyx densely pale brown woolly to pubescent.